Accuracy improvement of tropospheric delay correction models in space geodetic data. Case study: Egypt - Sobhy Abdel Monem Younes; Hafez Abbas Afify (Geodesy and Cartography, 2014)
The tropospheric delay still remains a limiting factor to the accuracy of space based positioning techniques. The estimation of station positioning, especially height component, which is particularly important for more applications is susceptible to errors in modeling the tropospheric delay due to correlations between the station positioning and residual troposphere delay parameters. As the demand on positioning accuracy and precision has increased, it has begun a necessary of relaying on large external data sets, rather than relatively simple models for treating the tropospheric delay. This method has been possible by advances made in numerical weather models which provide accurate representations of global atmospheric conditions and by advances in computing speed which allow us to perform a large number of computations over a short period of time. The purpose of this work is to develop a new model for estimating the tropospheric delay and then assess the benefits of applying this model at various geographic atmospheric conditions of Egypt. By comparing new model with some common models such as Saastamoinen model, Hopfield model, Niell-MF, Black & Eisner-MF, UNB3 model and Vienna-MF, the results show that, new model for estimation tropospheric delay has an acceptable level of accuracy in describing the dry tropospheric delay in Egypt as it agrees closely with the numerical integration based model. The mean accuracy of this new model has been assessed to be about 9.64 mm with rms 11 mm at an elevation angle of 30° and for an elevation angle of 5°, the mean accuracy is about 83.23 mm with rms 96.42 mm for atmospheric conditions of Egypt.